calculus

posted by .

find the derivative of the function f(x) = e^(3x) sec (7x)

  • calculus -

    It looks like you just need product rule. Start with the e^(3x). Keep it like that the multiply by the derivative of that sec function which is then sec(7x)tan(7x) . Next add the derivative of the e^(3x) times the regular function from the sec function. So step two is +3e^(3x) times sec(7x)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    find dy/dx y=ln (secx + tanx) Let u= secx + tan x dy/dx= 1/u * du/dx now, put the derivative of d secx/dx + dtanx/dx in. You may have some challenging algebra to simplify it. Use the chain rule. Let y(u) = ln u u(x) = sec x + tan x …
  2. calculus

    Please find the Derivative of the function y =sec^2x + tan^2x
  3. calculus

    find the derivative of the function f(x) = e^(3x) sec (7x)
  4. calculus

    Find the derivative of the function using the definition of derivative. g(t)= 9/sqrt(t) g'(t)= state the domain of the function and the domain of the derivative (use interval notation)
  5. Calculus 1A

    I am trying to find: dy/dx for y = sec(tan x) I have the answer, but I have no idea how to get there. I know that the derivative of sec x = sec x tan x and that the derivative of tan x is sec^2 x. But sec doesn't have an x, so ...?
  6. Calculus

    Hi. I need help with finding the derivative of the function: y= [(sec^7 x)/7] - [(sec^5 x)/5] Thanks!
  7. calculus

    1. Which of the following expressions is the definition of the derivative of f(x) = cos(x) at the point (2, cos(2))?
  8. Calculus

    1.) Find the derivative of tan (sec x). 2.) Find the derivative if 1/x in four ways, using the limit process, power rule, quotient rule and implicit differentiation. 3.) Show that the derivative of sec^-1 x is 1/(|x|*sqrt(x^2 -1)). …
  9. Calculus

    Differentiate to find critical numbers and leave function in fully factored form. g(x) = (x^2+1)^5(x^2+2)^6 g'(x) = (x^2+1)^5[6(x^2+2)^5(2x)] + (x^2+2)^6[5(x^2+1)^4(2x)] g'(x) = 2x(x^2+1)^4(x^2+2)^5[6(x^2+2)(2x) + 5(x^2+1)(2x)] g'(x) …
  10. Calculus

    Hello I need help with this excersise of derivative of a inverse function. The excersise says: If f(x+2)=x^3+1 and g(x)=f(arctg x), find the derivative of the inverse function of g(x) and then calculate (g^-1 (9))'[the derivative of …

More Similar Questions